PENGARUH PIJAT TUINA TERHADAP TINGKAT NAFSU MAKAN BALITA GIZI KURANG - Indah Wulaningsih; Novita Sari; Heny Wijayanti (Universitas Pesantren Tinggi Darul Ulum, 2022)
Malnutrition is the biggest nutritional problem found in Indonesia. The cause of malnutrition is not only the amount of consumption but also in the overall dietary pattern of under-five children who are not sufficiently needed. To determine the effect of tuina massage on appetite in toddlers. This research is quantitative using a Quasy Experimental design with the One Group Pre-Test-Post-Test Design approach. The population in this study was underfives with malnutrition in Public Health Center Kedungmundu with a total of 57 children under five. The sampling technique used in this study was purposive sampling. The appetite of toddlers before the massage tuina had an average of 5,812, standart of deviation was 0.655, and the lowest score was 5 and the highest score was 7, while after massage it was carried out on toddlers it had an average of 8,187 deviation standart of 0.910, and the lowest score was 7, the highest score was 10. The results of statistical tests showed that there was an effect of tuina massage on the increase in appetite for under-nutrition children with a p value of 0.000. The result of this study is that there is an effect of tuina massage on the increased appetite of toddlers after and before the tuina massage. Keywords: Tuina massage, Appetite, Toddler.